Oculopressor free subtenon anesthesia in cataract surgery - Ozden, S.; Ozkaya, U. (My University, 1993)
[Abstract Not Available]
Keywords: adrenalin; jetocaine; lidocaine; local anesthetic agent; unclassified drug; article; cataract extraction; clinical article; controlled study; human; intraocular pressure; retrobulbar anesthesia